Adhesive film for metal three-dimensional plate, preparation method of adhesive film and metal three-dimensional plate

By using a superposition structure and nanomagnesium hydroxide-modified glass fiber layer in the bonding film of the metal three-dimensional board, the problem of insufficient flame retardant performance and bonding strength of the existing hot melt adhesive film is solved, and high resistance is achieved The bonding effect with high mechanical properties and reduces production costs.

CN119391320AActive Publication Date: 2025-02-07GUANGZHOU LUSHAN NEW MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411987298.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-07
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When used for bonding of metal three-dimensional plates, the flame retardant performance does not meet the requirements, and the bonding strength is insufficient, resulting in the mechanical properties and service life of the three-dimensional plates not meeting the requirements.

Method used

The adhesive film arranged in sequence is provided with an adhesive film, including a first adhesive layer, a glass fiber layer and a second adhesive layer, each of which independently includes a specific component, a glass fiber The layer is modified by chemical grafting of nanomagnesium hydroxide to improve overall strength and flame retardant properties.

Benefits of technology

It improves the flame retardant performance of the adhesive film, reaches the B1 level, enhances the bonding strength, meets the flame retardant and mechanical performance requirements of three-dimensional boards in civil construction and vehicle and ship decoration fields, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391320A_ABST
    Figure CN119391320A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bonding materials, in particular to a bonding adhesive film for a metal three-dimensional plate, a preparation method of the bonding adhesive film and the metal three-dimensional plate. The adhesive film for the metal three-dimensional plate comprises a first adhesive layer, a glass fiber layer and a second adhesive layer which are sequentially overlapped, the first bonding layer and the second bonding layer comprise the following components: an ethylene-vinyl acetate copolymer, a graft of the ethylene-vinyl acetate copolymer, a thermoplastic elastomer, calcium stearate, polyethylene wax, magnesium hydroxide, high impact polystyrene and an antioxidant; the glass fiber layer comprises a glass fiber membrane and nano magnesium hydroxide grafted on the glass fiber membrane by a silane coupling agent. The adhesive film disclosed by the invention has excellent strength and flame retardant property, and can meet the requirements on flame retardant property and mechanical property of three-dimensional plates in the fields of civil buildings, vehicle and boat decoration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive materials, and in particular to an adhesive film for a metal three-dimensional plate, a preparation method thereof, and the metal three-dimensional plate. Background Art

[0002] Three-dimensional boards (or plates) as building materials, especially metal three-dimensional boards, have better mechanical strength, corrosion resistance, and long service life than traditional wood materials. They are increasingly widely used in civil construction, vehicle and ship decoration and other fields.

[0003] The aluminum panels and the middle core materials of existing three-dimensional panels are usually bonded with solvent-based glue. However, solvent-based glue takes a long time to process, is brittle, has a short service life and is not environmentally friendly. Hot melt adhesive film is increasingly favored by users of adhesive materials because of its advantages such as ease of use, good bonding performance and environmental protection.

[0004] Three-dimensional panels used in civil construction, vehicle and ship decoration, etc., not only require low cost and excellent mechanical properties, but also require flame retardancy of at least B1 level. However, the current hot melt adhesive film, on the one hand, does not meet the flame retardancy requirements; on the other hand, the bonding strength to metal three-dimensional panels is insufficient, resulting in the mechanical properties and service life of the three-dimensional panels not meeting the requirements.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One object of the present invention is to provide an adhesive film for a metal three-dimensional plate, which has both excellent flame retardant properties and excellent bonding properties to the metal three-dimensional plate.

[0007] Another object of the present invention is to provide a method for preparing an adhesive film for a metal three-dimensional plate.

[0008] Another object of the present invention is to provide a metal three-dimensional plate, comprising the above-mentioned adhesive film.

[0009] In order to achieve the above-mentioned object of the present invention, the present invention provides an adhesive film for a metal three-dimensional plate, comprising a first adhesive layer, a glass fiber layer and a second adhesive layer stacked in sequence; The first adhesive layer and the second adhesive layer each independently comprise the following components in parts by weight: 20-50 parts of ethylene-vinyl acetate copolymer, 10-20 parts of ethylene-vinyl acetate copolymer graft, 5-15 parts of thermoplastic elastomer, 1.5-2.5 parts of calcium stearate, 0.5-2.5 parts of polyethylene wax, 30-60 parts of magnesium hydroxide, 2-5 parts of high impact polystyrene and 0.1-0.5 parts of antioxidant; The glass fiber layer comprises a glass fiber membrane and nano magnesium hydroxide grafted onto the glass fiber membrane by a silane coupling agent; the preparation of the glass fiber layer comprises: immersing the glass fiber membrane in a suspension of nano magnesium hydroxide and then immersing it in a solution containing a silane coupling agent.

[0010] In a specific embodiment of the present invention, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane and γ-(2,3-glycidoxy)propyltrimethoxysilane.

[0011] In a specific embodiment of the present invention, the melting point of the ethylene-vinyl acetate copolymer is 60-90° C., the VA content is 28 wt %-40 wt %, and the melt index at 190° C. / 2.16 kg is 100-400 g / 10 min.

[0012] In a specific embodiment of the present invention, in the grafted product of ethylene-vinyl acetate copolymer, the relative grafting rate is 0.4% to 0.6%; the grafted monomer is an unsaturated polar monomer. Further, the unsaturated polar monomer includes at least one of maleic anhydride, diethyl maleate and butyl acrylate.

[0013] In a specific embodiment of the present invention, the melt index of the grafted ethylene-vinyl acetate copolymer is 30-50 g / 10 min at 190° C. / 2.16 kg.

[0014] In a specific embodiment of the present invention, the thermoplastic elastomer includes at least one of a styrene thermoplastic elastomer and a polyolefin thermoplastic elastomer. Further, the styrene thermoplastic elastomer includes at least one of SIS and SBS; the polyolefin thermoplastic elastomer includes at least one of ethylene-butene copolymer and ethylene-octene copolymer.

[0015] In a specific embodiment of the present invention, the thermoplastic elastomer includes a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:(2-5).

[0016] In a specific embodiment of the present invention, the mass ratio of the thermoplastic elastomer to the high impact polystyrene is (1-3):1.

[0017] In a specific embodiment of the present invention, the high impact polystyrene has a melt index of 7 to 10 g / 10 min at 200° C. / 5 kg.

[0018] In a specific embodiment of the present invention, the thickness of the adhesive film is 0.08-0.12 mm. Furthermore, the thickness ratio of the first adhesive layer, the glass fiber layer and the second adhesive layer is (0.4-0.6) : 1 : (0.4-0.6).

[0019] Another aspect of the present invention provides a method for preparing any one of the above-mentioned adhesive films for metal three-dimensional plates, comprising the following steps: preparing a first adhesive layer and a second adhesive layer on both sides of a glass fiber layer by a casting method.

[0020] Another aspect of the present invention provides a metal three-dimensional plate, comprising any one of the above-mentioned adhesive films.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The adhesive film of the present invention is provided by laminating an adhesive layer and a glass fiber layer, which can not only improve the overall strength of the film, but also further improve the flame retardant properties of the film and reduce the overall combustion calorific value of the film; (2) The present invention regulates the composition of the adhesive layer so that the adhesive layer has excellent initial bonding performance, bonding speed and bonding durability to the three-dimensional plate material, and has good bonding and fusion effects with the glass fiber layer; (3) The metal three-dimensional plate made by using the adhesive film of the present invention can meet the flame retardant and mechanical property requirements of the three-dimensional plate in the fields of civil construction, vehicle and ship decoration, etc. At the same time, the adhesive film of the present invention has low cost and is more conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 A schematic structural diagram of an adhesive film for a metal three-dimensional plate provided in an embodiment of the present invention.

[0024] Reference numerals: 1-first bonding layer; 2-glass fiber layer; 3-second bonding layer. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0027] Figure 1 A schematic diagram of the structure of an adhesive film for a metal three-dimensional plate provided in an embodiment of the present invention, as shown in FIG. Figure 1 As shown, the adhesive film provided in this embodiment includes a first adhesive layer 1, a glass fiber layer 2 and a second adhesive layer 3 which are stacked in sequence.

[0028] The first adhesive layer 1 and the second adhesive layer 3 each independently include the following components in parts by weight: 20-50 parts of ethylene-vinyl acetate copolymer (EVA), 10-20 parts of EVA grafts, 5-15 parts of thermoplastic elastomers, 1.5-2.5 parts of calcium stearate, 0.5-2.5 parts of polyethylene wax, 30-60 parts of magnesium hydroxide, 2-5 parts of high-impact polystyrene and 0.1-0.5 parts of antioxidants; the glass fiber layer 2 is a glass fiber film with nano-magnesium hydroxide chemically grafted on the surface.

[0029] The glass fiber layer 2 includes a glass fiber membrane and nano-magnesium hydroxide grafted onto the glass fiber membrane by a silane coupling agent. The preparation of the glass fiber layer includes: immersing the glass fiber membrane in a suspension of nano-magnesium hydroxide and then immersing it in a solution containing a silane coupling agent.

[0030] It should be noted that the compositions of the first adhesive layer 1 and the second adhesive layer 3 of the present invention may be the same, or different while each satisfying the above-mentioned component requirements.

[0031] The adhesive film of the present invention is configured by stacking an adhesive layer and a glass fiber layer, which can not only improve the overall strength of the film, but also further reduce the overall combustion calorific value of the film, thereby improving the flame retardant performance of the film. The flame retardant performance can reach B1 level, meeting the use requirements in the fields of civil construction, vehicle and ship decoration, etc.

[0032] The first adhesive layer and the second adhesive layer of the present invention introduce a certain amount of high-impact polystyrene, which effectively reduces the overall cohesive strength of the material and is conducive to improving the bonding speed of the material; combined with a certain amount of thermoplastic elastomer, the wetting effect on the three-dimensional board core material can be greatly improved, the bonding durability of the adhesive layer can be improved, and the overall compatibility of the material can be enhanced, so that it has good initial bonding performance during the composite process, thereby improving the bonding speed and bonding strength. In addition, the resin matrix in the first adhesive layer and the second adhesive layer adopts EVA, which has the characteristics of low melting point and high melting index, which is not only conducive to processing, but also conducive to its bonding and fusion with the glass fiber layer.

[0033] A large amount of magnesium hydroxide is used in the first adhesive layer and the second adhesive layer of the present invention to improve the flame retardancy, and an EVA graft is introduced into the adhesive layer to improve the compatibility between the resin matrix and the magnesium hydroxide, and to improve the tensile strength of the adhesive layer; polyethylene wax and calcium stearate are further introduced into the adhesive layer to improve the internal and external lubricity of the adhesive layer material, further improve the compatibility and processability of the adhesive layer material, and make subsequent processing such as extrusion smoother.

[0034] For example, in different embodiments, the amounts of the components in the first adhesive layer and the second adhesive layer may be independently as follows, in parts by weight: The amount of EVA can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts or a range consisting of any two of them; The amount of the grafted EVA can be 10 parts, 12 parts, 15 parts, 18 parts, 20 parts or any two of them; The amount of the thermoplastic elastomer can be 5 parts, 8 parts, 10 parts, 12 parts, 15 parts or a range consisting of any two of them; The amount of calcium stearate can be 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or a range consisting of any two of them; The amount of polyethylene wax can be 0.5 parts, 0.8 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts or a range consisting of any two of them; The amount of magnesium hydroxide can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or a range consisting of any two of them; The amount of high impact polystyrene can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any two thereof; The dosage of the antioxidant can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part or a range consisting of any two of them, wherein the antioxidant includes but is not limited to at least one of antioxidant B215, antioxidant B245, and antioxidant 1010.

[0035] The present invention adopts a glass fiber membrane modified by chemical grafting of nano magnesium hydroxide as the middle layer. On the one hand, the glass fiber membrane does not burn, and on the other hand, the modification of nano magnesium hydroxide helps to improve the overall strength and flame retardancy of the membrane material, so that the adhesive film of the present invention has excellent strength and high flame retardancy.

[0036] In a specific embodiment of the present invention, the preparation of the glass fiber layer includes: dipping the glass fiber membrane in a suspension of nano-magnesium hydroxide, and then dipping it in a solution containing a silane coupling agent. Further, in the suspension of nano-magnesium hydroxide, the mass fraction of nano-magnesium hydroxide is 0.1% to 0.3%; in the solution containing a silane coupling agent, the mass fraction of the silane coupling agent is 0.05% to 0.15%.

[0037] After being immersed in a suspension of nano-magnesium hydroxide, the nano-magnesium hydroxide is attached to the surface of the glass fiber layer; then immersed in a solution containing a silane coupling agent, the silane coupling agent is hydrolyzed to produce a silanol group, which can be polycondensed with the hydroxyl group on the surface of the nano-magnesium hydroxide of the glass fiber membrane, and then the nano-magnesium hydroxide is grafted to the surface of the glass fiber membrane in a chemically bonded manner, significantly improving the interfacial properties of the glass fiber layer. For example, in different embodiments, in the suspension of nano-magnesium hydroxide, the mass fraction of nano-magnesium hydroxide can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or a range consisting of any two of them. In a solution containing a silane coupling agent, the mass fraction of the silane coupling agent can be 0.05%, 0.08%, 0.1%, 0.12%, 0.15% or a range consisting of any two of them.

[0038] In a specific embodiment of the present invention, the solvent in the suspension of nano magnesium hydroxide is an ethanol aqueous solution. Further, in the ethanol aqueous solution, the mass fraction of ethanol is 70% to 80%.

[0039] In a specific embodiment of the present invention, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane. In the solution containing the silane coupling agent, the solvent used can be a mixture of alcohol and water, wherein the alcohol includes but is not limited to at least one of methanol, ethanol and isopropanol. Furthermore, the mass ratio of alcohol to water is (8-10) : 1, such as 9: 1.

[0040] In a specific embodiment of the present invention, the immersion time in the suspension of nano-magnesium hydroxide is 0.2 to 0.5 h, such as 0.2 h, 0.3 h, 0.4 h, 0.5 h, etc.; the immersion time in the solution containing a silane coupling agent is 0.5 to 1 h, such as 0.5 h, 0.6 h, 0.8 h, 1 h, etc.

[0041] In actual operation, the preparation of the glass fiber layer may include the following steps: (1) treating nano-magnesium hydroxide in ethanol with ultrasound to obtain a suspension of nano-magnesium hydroxide; (2) placing the glass fiber membrane in the suspension of nano magnesium hydroxide prepared in step (1) for 0.2 to 0.5 h, and then taking it out and drying it; (3) The glass fiber membrane treated in step (2) is placed in a solution containing a silane coupling agent for 0.5 to 1 hour, and then taken out and dried to obtain a glass fiber layer.

[0042] Nano magnesium hydroxide powder has excellent specific surface area and high surface activity. When dispersed by ultrasound, its cavitation effect is more conducive to the dispersion and deagglomeration of nano magnesium hydroxide.

[0043] In a specific embodiment of the present invention, the melting point of EVA is 60-90° C., the VA content is 28 wt %-40 wt %, and the melt index at 190° C. / 2.16 kg is 100-400 g / 10 min.

[0044] The use of EVA with a low melting point and a high melting index is more conducive to improving the processing performance of the adhesive layer and ensuring its bonding and fusion with the glass fiber layer. For example, in different embodiments, the melting point of EVA can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or a range consisting of any two thereof; the VA content in EVA can be 28wt%, 30wt%, 32wt%, 35wt%, 38wt%, 40wt% or a range consisting of any two thereof; the melting index of EVA at 190°C / 2.16kg can be 100g / 10min, 150g / 10min, 200g / 10min, 250g / 10min, 300g / 10min, 350g / 10min, 400g / 10min or a range consisting of any two thereof.

[0045] In a specific embodiment of the present invention, in the grafted product of EVA, the relative grafting rate is 0.4% to 0.6%; the grafting monomer is an unsaturated polar monomer. Further, the unsaturated polar monomer includes at least one of maleic anhydride, diethyl maleate and butyl acrylate.

[0046] For example, in different embodiments, the relative grafting rate may be 0.4%, 0.45%, 0.5%, 0.55%, 0.6% or a range consisting of any two thereof.

[0047] In a specific embodiment of the present invention, the melt index of the EVA grafted product at 190° C. / 2.16 kg is 30-50 g / 10 min.

[0048] For example, in different embodiments, the melt index of the EVA graft at 190° C. / 2.16 kg can be 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min, or a range consisting of any two of them.

[0049] In a specific embodiment of the present invention, the EVA graft is mainly prepared by 100 parts of EVA, 1.5-3 parts of graft monomer and 0.2-0.25 parts of initiator by weight. In actual operation, the preparation of the EVA graft includes: mixing EVA, graft monomer and initiator uniformly, and extruding and granulating. Furthermore, the extrusion granulation temperature can be 150-170°C.

[0050] Wherein, the initiator includes dicumyl peroxide and / or 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0051] In a specific embodiment of the present invention, the thermoplastic elastomer includes at least one of a styrene thermoplastic elastomer and a polyolefin thermoplastic elastomer. Further, the styrene thermoplastic elastomer includes at least one of SIS and SBS; the polyolefin thermoplastic elastomer includes at least one of an ethylene-butene copolymer and an ethylene-octene copolymer.

[0052] Among them, the melt index of polyolefin thermoplastic elastomer at 190℃ / 2.16kg is 30-50g / 10min, the melting point is 50-100℃, and the density is 0.86-0.88g / cm 3 The melting point of styrene thermoplastic elastomer at 190°C / 2.16kg is 2-4g / 10min, and the melting point is 80-90°C.

[0053] In a specific embodiment of the present invention, the thermoplastic elastomer includes a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:(2-5).

[0054] For example, in different embodiments, in the thermoplastic elastomer, the mass ratio of styrene-based thermoplastic elastomer to polyolefin-based thermoplastic elastomer can be 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:4, 1:5 or a range consisting of any two of them. The use of the above-mentioned thermoplastic elastomer can improve both the material processing performance and weather resistance.

[0055] In a specific embodiment of the present invention, the mass ratio of thermoplastic elastomer to high impact polystyrene is (1-3):1.

[0056] For example, in different embodiments, the mass ratio of thermoplastic elastomer to high impact polystyrene can be 1:1, 1.2:1, 1.5:1, 2:1, 2.5:1, 3:1 or any two thereof. The amount of thermoplastic elastomer and high impact polystyrene is adjusted to meet the above conditions, which can improve the initial adhesion performance, bonding speed and strength; when the ratio exceeds the above range, the cohesive strength is too low and the initial peel strength is significantly reduced.

[0057] In a specific embodiment of the present invention, the melt index of the high impact polystyrene at 200° C. / 5 kg is 7 to 10 g / 10 min.

[0058] In a specific embodiment of the present invention, the calcium stearate 0.075 mm sieve pass rate is ≥99.5 wt %.

[0059] In a specific embodiment of the present invention, the number average molecular weight of the polyethylene wax is 2000-3000.

[0060] In a specific embodiment of the present invention, the mesh size of the magnesium hydroxide is 325 to 1200 meshes.

[0061] For example, in different embodiments, the mesh size of the magnesium hydroxide can be 325 mesh, 400 mesh, 500 mesh, 600 mesh, 800 mesh, 1000 mesh, 1200 mesh, or a range consisting of any two of them.

[0062] In a specific embodiment of the present invention, the thickness of the adhesive film is 0.08-0.12 mm. Furthermore, the thickness ratio of the first adhesive layer, the glass fiber layer and the second adhesive layer is (0.4-0.6) : 1 : (0.4-0.6).

[0063] Another aspect of the present invention provides a method for preparing any one of the above-mentioned adhesive films for metal three-dimensional plates, comprising the following steps: preparing a first adhesive layer and a second adhesive layer on both sides of a glass fiber layer by a casting method.

[0064] In actual operation, the raw materials of the first adhesive layer and the second adhesive layer can be co-extruded and cast onto both sides of the glass fiber layer through a double die head. The glass fiber layer is unwound in the middle of the double casting die head through a unwinding roller to obtain a composite layer structure of the first adhesive layer, the glass fiber layer and the second adhesive layer. The composite layer structure is then cooled, shaped and rolled up to obtain an adhesive film for metal three-dimensional plates.

[0065] In a specific embodiment of the present invention, hot melt adhesive particles of the first adhesive layer and hot melt adhesive particles of the second adhesive layer are respectively prepared in advance according to the composition ratio of the first adhesive layer and the second adhesive layer. The preparation method of the hot melt adhesive particles comprises: premixing the raw materials of each layer in proportion through a high-speed mixer, and then kneading through a twin-screw extruder to obtain the corresponding hot melt adhesive particles.

[0066] In a specific embodiment of the present invention, the extrusion temperature of the twin-screw extruder is 190-200°C.

[0067] In a specific embodiment of the present invention, the casting temperature is 200-220°C.

[0068] Another aspect of the present invention provides a metal three-dimensional plate, comprising any one of the above-mentioned adhesive films.

[0069] In a specific embodiment of the present invention, the metal three-dimensional plate includes a metal bottom plate, a three-dimensional core plate and a metal face plate, and each layer is bonded by an adhesive film.

[0070] Example 1 This embodiment provides an adhesive film for a metal three-dimensional plate, and its structure is as follows: Figure 1 As shown, the thickness of the first adhesive layer 1 is 0.02 mm, the thickness of the glass fiber layer 2 is 0.04 mm, and the thickness of the second adhesive layer 3 is 0.02 mm.

[0071] The first adhesive layer and the second adhesive layer both include the following components in parts by weight: EVA 45 parts, EVA graft 15 parts, thermoplastic elastomer 5 parts, calcium stearate 1.5 parts, polyethylene wax 0.5 parts, magnesium hydroxide 30 parts, high impact polystyrene 5 parts and antioxidant 0.25 parts; Among them, the melting point of EVA is 80℃, the VA content is 28wt%, and the melting index under 190℃ / 2.16kg is 100g / 10min; In the grafted material of EVA, the relative grafting rate of monomer maleic anhydride is 0.4%, and the melt index of the grafted material under the condition of 190℃ / 2.16kg is 30g / 10min; the grafted material of EVA is prepared by premixing the above-mentioned EVA, maleic anhydride, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane in a high mixer at a mass ratio of 100:1.5:0.2, and then extruding and granulating by a reactive twin-screw extruder. During the extrusion granulation, the main engine speed is 300-400rpm (such as 350rpm), the aspect ratio of the extruder is ≥42:1, and the extrusion processing temperature is 150-170℃; The thermoplastic elastomer is an ethylene-butene copolymer with a melt index of 30 g / 10 min at 190 °C / 2.16 kg, a melting point of 65 °C, and a density of 0.872 g / cm 3 ; The melt index of high-impact polystyrene at 200°C / 5kg is 7g / 10min; The mesh number of magnesium hydroxide is 325 mesh; the passing rate of calcium stearate through 0.075mm sieve is ≥99.5wt%; the number average molecular weight of polyethylene wax is 1000; The antioxidant includes antioxidant B215 and antioxidant B245 in a mass ratio of 1:1.

[0072] The preparation of the glass fiber layer includes: (1) treating nano-magnesium hydroxide in an ethanol aqueous solution having a mass fraction of 70% by ultrasonic wave to obtain a nano-magnesium hydroxide suspension having a nano-magnesium hydroxide concentration of 0.2 wt %; (2) Take a 0.05 mm thick glass fiber membrane (GF-B, 2400 tex), place it in the suspension of nano magnesium hydroxide prepared in step (1) for 0.2 h, and then take it out and dry it at 60 ° C for 1 h; (3) The glass fiber membrane treated in step (2) is placed in a solution of a silane coupling agent (γ-aminopropyltriethoxysilane) with a mass fraction of 0.05% for 0.5 h, and then taken out and dried at 60° C. for 1 h to obtain a glass fiber layer. The preparation of the 0.05% silane coupling agent solution includes: taking 5 parts by weight of the silane coupling agent, 85.5 parts by weight of ethanol, and 9.5 parts by weight of water and mixing them evenly.

[0073] This embodiment provides a method for preparing an adhesive film for a metal three-dimensional plate, comprising the following steps: (a) The raw materials required for the first adhesive layer and the second adhesive layer are premixed in a high-speed mixer for 20 to 30 minutes according to the following ratio, and then kneaded through a twin-screw extruder to obtain hot melt adhesive particles for the first adhesive layer and the second adhesive layer; wherein the auxiliary agent speed of the twin-screw extruder is 400 rpm, the aspect ratio of the twin-screw extruder L:D ≥ 52:1 (e.g., 52:1), and the extrusion processing temperatures from the first zone to the eighth zone are: 120°C, 150°C, 180°C, 190°C, 190°C, 200°C, 200°C, 200°C, respectively.

[0074] (b) The hot melt adhesive particles of the first adhesive layer and the second adhesive layer are co-extruded and cast onto both sides of the glass fiber layer through a double die head; specifically, the glass fiber layer is unwound in the middle of the double casting die head through an unwinding roller to obtain a composite layer structure of the first adhesive layer / glass fiber layer / first adhesive layer, which is then cooled, shaped and rolled up to obtain an adhesive film for metal three-dimensional plates.

[0075] Example 2 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, and the only difference is that the raw material composition of the first adhesive layer and the second adhesive layer is different.

[0076] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: EVA 40 parts, EVA graft 17 parts, thermoplastic elastomer 10 parts, calcium stearate 1.5 parts, polyethylene wax 0.5 parts, magnesium hydroxide 29 parts, high impact polystyrene 2 parts and antioxidant 0.25 parts; Among them, EVA includes EVA-1 and EVA-2 with a mass ratio of 3:2; the melting point of EVA-1 is 62°C, the VA content is 28wt%, and the melt index under the condition of 190°C / 2.16kg is 100g / 10min; the melting point of EVA-2 is 90°C, the VA content is 35wt%, and the melt index under the condition of 190°C / 2.16kg is 200g / 10min; In the grafted EVA, the relative graft rate of monomer maleic anhydride is 0.45%, and the melt index of the grafted EVA under the condition of 190°C / 2.16kg is 40g / 10min; the grafted EVA is prepared by premixing the above-mentioned EVA-1, EVA-2, maleic anhydride, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane in a high mixer at a mass ratio of 60:40:1.5:0.25, and then extruding and granulating the mixture through a reactive twin-screw extruder. During the extrusion granulation, the main engine speed is 300-400rpm (e.g., 350rpm), the aspect ratio of the extruder is ≥42:1, and the extrusion processing temperature is 150-170°C; The thermoplastic elastomer is an ethylene-octene copolymer with a melt index of 33 g / 10 min at 190 °C / 2.16 kg, a melting point of 62 °C, and a density of 0.882 g / cm 3 ; The melt index of high-impact polystyrene at 200°C / 5kg is 7.5g / 10min; The mesh number of magnesium hydroxide is 800 mesh; the passing rate of calcium stearate through 0.075mm sieve is ≥99.5wt%; and the number average molecular weight of polyethylene wax is 1000.

[0077] Example 3 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, and the only difference is that the raw material composition of the first adhesive layer and the second adhesive layer is different.

[0078] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: EVA 30 parts, EVA graft 20 parts, thermoplastic elastomer 10 parts, calcium stearate 1.5 parts, polyethylene wax 0.5 parts, magnesium hydroxide 36 parts, high impact polystyrene 2 parts and antioxidant 0.25 parts; Among them, EVA includes EVA-1 and EVA-3 with a mass ratio of 3:7; the melting point of EVA-1 is 62°C, the VA content is 28wt%, and the melt index at 190°C / 2.16kg is 100g / 10min; the melting point of EVA-3 is 75°C, the VA content is 35wt%, and the melt index at 190°C / 2.16kg is 400g / 10min; In the grafted EVA, the relative graft rate of monomer maleic anhydride is 0.44%, and the melt index of the grafted EVA under the condition of 190°C / 2.16kg is 50g / 10min; the grafted EVA is prepared by premixing the above-mentioned EVA-1, EVA-3, maleic anhydride, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane in a high mixer at a mass ratio of 30:70:2:0.25, and then extruding and granulating the mixture through a reactive twin-screw extruder. During the extrusion granulation, the main engine speed is 300-400rpm (e.g., 350rpm), the aspect ratio of the extruder is ≥42:1, and the extrusion processing temperature is 150-170°C; The thermoplastic elastomer is an ethylene-octene copolymer with a melt index of 33 g / 10 min at 190 °C / 2.16 kg, a melting point of 62 °C, and a density of 0.882 g / cm 3 ; The melt index of high-impact polystyrene at 200°C / 5kg is 7.5g / 10min; The mesh number of magnesium hydroxide is 1250 mesh; the passing rate of calcium stearate through 0.075mm sieve is ≥99.5wt%; the number average molecular weight of polyethylene wax is 1000; The antioxidant is B215.

[0079] Example 4 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, and the only difference is that the raw material composition of the first adhesive layer and the second adhesive layer is different.

[0080] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: EVA 35 parts, EVA graft 15 parts, thermoplastic elastomer 8 parts, calcium stearate 1 part, polyethylene wax 0.5 parts, magnesium hydroxide 36 parts, high impact polystyrene 5 parts and antioxidant 0.25 parts; Among them, the melting point of EVA is 87℃, the VA content is 35wt%, and the melt index at 190℃ / 2.16kg is 400g / 10min; In the grafted material of EVA, the relative grafting rate of monomer maleic anhydride is 0.45%, and the melt index of the grafted material under the condition of 190℃ / 2.16kg is 48g / 10min; the grafted material of EVA is prepared by premixing the above-mentioned EVA, maleic anhydride, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane in a high mixer at a mass ratio of 100:2.5:0.25, and then extruding and granulating with a reactive twin-screw extruder. During the extrusion granulation, the main engine speed is 300-400rpm (such as 350rpm), the aspect ratio of the extruder is ≥42:1, and the extrusion processing temperature is 150-170℃; The thermoplastic elastomer includes ethylene-butene copolymer and SIS in a mass ratio of 2:1; wherein the ethylene-butene copolymer has a melt index of 30 g / 10 min at 190°C / 2.16 kg, a melting point of 70°C, and a density of 0.880 g / cm 3 SIS, the melting point is 90°C, and the melting point is 3g / 10min at 190°C / 2.16kg. When used, the ethylene-butene copolymer and SIS are pre-blended in proportion and then extruded and granulated by a single screw extruder. The extrusion granulation temperature is 170-190°C. The melt index of high-impact polystyrene at 200°C / 5kg is 7.5g / 10min; The mesh number of magnesium hydroxide is 325 mesh; the passing rate of calcium stearate through 0.075mm sieve is ≥99.5wt%; the number average molecular weight of polyethylene wax is 1000; The antioxidant is B215.

[0081] Example 5 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, and the only difference is that the raw material composition of the first adhesive layer and the second adhesive layer is different.

[0082] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: EVA 30 parts, EVA graft 20 parts, thermoplastic elastomer 8 parts, calcium stearate 1 part, polyethylene wax 0.5 parts, magnesium hydroxide 39 parts, high impact polystyrene 2 parts and antioxidant 0.25 parts; Among them, EVA includes EVA-2 and EVA-3 with a mass ratio of 1:1; the melting point of EVA-2 is 90°C, the VA content is 35wt%, and the melt index at 190°C / 2.16kg is 200g / 10min; the melting point of EVA-3 is 75°C, the VA content is 35wt%, and the melt index at 190°C / 2.16kg is 400g / 10min; In the grafted material of EVA, the relative grafting rate of monomer maleic anhydride is 0.43%, and the melt index of the grafted material under the condition of 190℃ / 2.16kg is 47g / 10min; the grafted material of EVA is prepared by premixing the above-mentioned EVA-2, EVA-3, maleic anhydride, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane in a high mixer at a mass ratio of 50﹕50﹕2﹕0.25, and then extruding and granulating with a reactive twin-screw extruder. During the extrusion granulation, the main engine speed is 300-400rpm (such as 350rpm), the aspect ratio of the extruder is ≥42﹕1, and the extrusion processing temperature is 150-170℃; The thermoplastic elastomer includes ethylene-butene copolymer and SIS in a mass ratio of 3:1; wherein the ethylene-butene copolymer has a melt index of 35 g / 10 min at 190°C / 2.16 kg, a melting point of 55°C, and a density of 0.880 g / cm 3 SIS, the melting point at 190℃ / 2.16kg is 3g / 10min, and the melting point is 90℃; The melt index of high-impact polystyrene at 200°C / 5kg is 8g / 10min; The mesh number of magnesium hydroxide is 325 mesh; the passing rate of calcium stearate through 0.075mm sieve is ≥99.5wt%; and the number average molecular weight of polyethylene wax is 1000.

[0083] Example 6 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, the only difference being that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Embodiment 1.

[0084] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components by weight: 20 parts of EVA, 13 parts of EVA graft, 5 parts of thermoplastic elastomer, 1.5 parts of calcium stearate, 2.5 parts of polyethylene wax, 60 parts of magnesium hydroxide, 2 parts of high impact polystyrene and 0.1 parts of antioxidant.

[0085] Example 7 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, the only difference being that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Embodiment 1.

[0086] In this embodiment, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: 40 parts of EVA, 10 parts of EVA graft, 15 parts of thermoplastic elastomer, 2.5 parts of calcium stearate, 0.5 parts of polyethylene wax, 30 parts of magnesium hydroxide, 5 parts of high impact polystyrene and 0.1 parts of antioxidant.

[0087] Example 8 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, the only difference being that the thermoplastic elastomers used in the first adhesive layer and the second adhesive layer are different, and the rest are the same as Embodiment 1.

[0088] The thermoplastic elastomer of this embodiment includes a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:2; the styrene-based thermoplastic elastomer is SIS (the same SIS used in Example 4), and the polyolefin-based thermoplastic elastomer is an ethylene-butene copolymer (the same ethylene-butene copolymer used in Example 1). The method of blending and extrusion granulation of the two is as described in Example 4.

[0089] Example 9 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, the only difference being that the thermoplastic elastomers used in the first adhesive layer and the second adhesive layer are different, and the rest are the same as Embodiment 1.

[0090] The thermoplastic elastomer of this embodiment includes a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:3; the styrene-based thermoplastic elastomer is SIS (the same SIS used in Example 4), and the polyolefin-based thermoplastic elastomer is an ethylene-butene copolymer (the same ethylene-butene copolymer used in Example 1). The method of blending and extrusion granulation of the two is as described in Example 4.

[0091] Example 10 This embodiment refers to the adhesive film for metal three-dimensional plate and the preparation method thereof of Embodiment 1, the only difference being that the thermoplastic elastomers used in the first adhesive layer and the second adhesive layer are different, and the rest are the same as Embodiment 1.

[0092] The thermoplastic elastomer of this embodiment includes a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:5; the styrene-based thermoplastic elastomer is SIS (the same as the SIS used in Example 4), and the polyolefin-based thermoplastic elastomer is an ethylene-butene copolymer (the same as the ethylene-butene copolymer used in Example 1). The method of blending and extruding the two is referred to Example 4.

[0093] Embodiment 11 This embodiment refers to the adhesive film for metal three-dimensional plates and its preparation method of Example 8, with the only difference being that the amounts of thermoplastic elastomer and high-impact polystyrene used in the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 8.

[0094] In the first adhesive layer and the second adhesive layer of this embodiment, the amount of the thermoplastic elastomer is 7 parts, and the amount of the high-impact polystyrene is 3 parts.

[0095] Example 12 This embodiment refers to the adhesive film for metal three-dimensional plates and its preparation method of Example 8, with the only difference being that the amounts of thermoplastic elastomer and high-impact polystyrene used in the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 8.

[0096] In the first adhesive layer and the second adhesive layer of this embodiment, the amount of the thermoplastic elastomer is 8 parts, and the amount of the high-impact polystyrene is 2 parts.

[0097] Comparative Example 1 Comparative Example 1 refers to the adhesive film and preparation method thereof of Example 1, except that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 1.

[0098] In Comparative Example 1, neither the first adhesive layer nor the second adhesive layer includes a thermoplastic elastomer, and the reduced amount of the thermoplastic elastomer is replaced by EVA or the like by weight.

[0099] Comparative Example 2 Comparative Example 2 refers to the adhesive film and preparation method thereof of Example 1, except that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 1.

[0100] In Comparative Example 2, high-impact polystyrene is not included in the first adhesive layer and the second adhesive layer, and the reduced amount of high-impact polystyrene is replaced by EVA or the like by weight.

[0101] Comparative Example 3 Comparative Example 3 refers to the adhesive film and preparation method thereof of Example 1, except that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 1.

[0102] In Comparative Example 3, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: 45 parts of EVA, 15 parts of EVA graft, 5 parts of thermoplastic elastomer, 1.5 parts of calcium stearate, 0.5 parts of polyethylene wax, 30 parts of magnesium hydroxide, 8 parts of high impact polystyrene and 0.25 parts of antioxidant.

[0103] Comparative Example 4 Comparative Example 4 refers to the adhesive film and preparation method thereof of Example 1, except that the raw material compositions of the first adhesive layer and the second adhesive layer are different, and the rest are the same as Example 1.

[0104] In Comparative Example 4, the first adhesive layer and the second adhesive layer both include the following components in parts by weight: 45 parts of EVA, 15 parts of EVA grafts, 5 parts of thermoplastic elastomer, 1.5 parts of calcium stearate, 0.5 parts of polyethylene wax, 30 parts of magnesium hydroxide, 1 part of high impact polystyrene and 0.25 parts of antioxidant.

[0105] Comparative Example 5 Comparative Example 5 refers to the adhesive film and preparation method thereof of Example 1, except that the glass fiber layer is different, and the rest of the parts are the same as Example 1.

[0106] Comparative Example 5 is a glass fiber layer that has not been subjected to modification treatment; that is, the glass fiber membrane in Example 1 is used as the glass fiber layer.

[0107] Comparative Example 6 Comparative Example 6 refers to the adhesive film and preparation method thereof of Example 1, except that the glass fiber layer is different, and the rest of the parts are the same as Example 1.

[0108] In Comparative Example 6, the glass fiber membrane treated in step (2) of Example 1 was used as the glass fiber layer.

[0109] Comparative Example 7 The main components of the commercially available hot melt adhesive film 1 are a blend of LLDPE, POE and calcium carbonate, with LLDPE accounting for 50%, POE accounting for 30% and calcium carbonate accounting for 20% by weight. The product uses conventional cast molding, a single-layer structure, and a film thickness of 0.10 mm.

[0110] Comparative Example 8 The main components of the commercially available hot melt adhesive film 2 are EVA, LLDPE, POE, and TPU. The product uses a blown film method and has a three-layer structure. The first and third layers have the same composition and proportion. In terms of weight percentage, EVA accounts for 20%, LLDPE accounts for 40%, POE accounts for 20%, and TPU accounts for 20%. The second layer is 100% LLDPE, and the thickness ratio of the three layers is 1:1:1. The thickness of the adhesive film is 0.12mm.

[0111] Experimental example In order to compare and illustrate the performance of the adhesive films of different embodiments and comparative examples, the adhesive films of various embodiments and comparative examples were subjected to the following tests. The test results are shown in Table 1.

[0112] Among them, the roller peel strength is tested according to the GB / T1457-2022 method; The film combustion calorific value is tested according to the GB / T14402-2007 method; The combustion grade is tested with reference to GB 8624-2012.

[0113] Table 1 Test results of different adhesive films

[0114] From the above test results, it can be seen that the adhesive film of the present invention uses an adhesive layer and a glass fiber layer to stack, which can not only improve the overall strength of the film, but also further improve the flame retardant performance of the film, which can reach B1 level, reduce the overall combustion calorific value of the film, and meet the flame retardant and mechanical performance requirements of three-dimensional panels in the fields of civil construction, vehicle and ship decoration, etc. At the same time, the adhesive film of the present invention has a low cost and is more conducive to large-scale production and application.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adhesive film for metal three-dimensional plates, characterized in that: It comprises a first bonding layer, a glass fiber layer and a second bonding layer which are stacked in sequence; The first adhesive layer and the second adhesive layer each independently comprise the following components in parts by weight: 20-50 parts of ethylene-vinyl acetate copolymer, 10-20 parts of ethylene-vinyl acetate copolymer graft, 5-15 parts of thermoplastic elastomer, 1.5-2.5 parts of calcium stearate, 0.5-2.5 parts of polyethylene wax, 30-60 parts of magnesium hydroxide, 2-5 parts of high impact polystyrene and 0.1-0.5 parts of antioxidant; The glass fiber layer includes a glass fiber membrane and nano magnesium hydroxide grafted onto the glass fiber membrane by a silane coupling agent; The preparation of the glass fiber layer comprises: the glass fiber membrane is immersed in a suspension of nano magnesium hydroxide, and then immersed in a solution containing a silane coupling agent.

2. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane and γ-(2,3-glycidoxy)propyltrimethoxysilane.

3. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer has at least one of the following characteristics: (1) Melting point is 60-90°C; (2) VA content is 28wt% to 40wt%; (3) The melt index at 190℃ / 2.16kg is 100-400g / 10min.

4. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The graft of ethylene-vinyl acetate copolymer has at least one of the following characteristics: (1) The relative grafting rate is 0.4% to 0.6%; (2) The grafting monomer is an unsaturated polar monomer; the unsaturated polar monomer includes at least one of maleic anhydride, diethyl maleate and butyl acrylate; (3) The melt index at 190℃ / 2.16kg is 30-50g / 10min.

5. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The thermoplastic elastomer includes at least one of a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer; The styrene-based thermoplastic elastomer includes at least one of SIS and SBS; The polyolefin-based thermoplastic elastomer includes at least one of an ethylene-butene copolymer and an ethylene-octene copolymer.

6. The adhesive film for metal three-dimensional plate according to claim 5, characterized in that: The thermoplastic elastomer comprises a styrene-based thermoplastic elastomer and a polyolefin-based thermoplastic elastomer in a mass ratio of 1:(2-5).

7. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The mass ratio of the thermoplastic elastomer to the high impact polystyrene is (1-3):1; The high impact polystyrene has a melting point of 7 to 10 g / 10 min at 200° C. / 5 kg.

8. The adhesive film for metal three-dimensional plate according to claim 1, characterized in that: The thickness of the adhesive film is 0.08 to 0.12 mm; The thickness ratio of the first adhesive layer, the glass fiber layer and the second adhesive layer is (0.4-0.6) : 1 : (0.4-0.6).

9. The method for preparing an adhesive film for a metal three-dimensional plate according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: preparing a first bonding layer and a second bonding layer respectively on both sides of a glass fiber layer by using a casting method.

10. A three-dimensional metal plate, characterized in that: The invention comprises the adhesive film for metal three-dimensional plates as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • High performance glass fiber tape adhesive and preparation method thereof

    CN108384489A

  • Thermoplastic micro-foaming low-smoke halogen-free flame-retarding cable material and preparation method thereof

    CN110872416A

  • Anti-crack flame-retardant double-sided glass fiber adhesive tape and preparation method thereof

    CN118421210A

  • Insulation protection composite belt, preparation method and application

    CN118956275A

  • Hot-melt film for trim material for automobile

    JP2002012840A